Optofluidic manipulation and sorting of nanoparticle and biomolecules - Zhao, Haitao (2018)
This doctorate thesis focuses on integrated Lab-on-a-chip functionalities stimulated by the unprecedented light-matter interaction in optofluidics. Specifically, three aspects of this subject is investigated. Firstly, an optofluidic waveguide sensor to monitor chemical reaction and measure diffusion coefficient is developed based on the light focusing pattern in optofluidic waveguides. The hydrolysis of sucrose is studied and the initial hydrolysis rate is determined to be 19.81 μmol/min. The diffusion coefficient of ethylene glycol-water solution is also measured experimentally. Secondly, an optofluidic hyperbolic secant lens is developed to improve the focusing power. The optimized index profile is derived based on coordinate transformation to suppress the optical aberrations. The focal lengths are investigated experimentally at different divergence angles and off-axis positions. The focusing experiment with multiple light sources is also conducted. Third, a photonic pillar array-based optofluidic manipulation system is developed based on waveguide-pair arrays for nanoparticle and bacteria manipulation. 500-nm polystyrene particle are separated out from 200-nm and 300-nm particle mixtures with a recovery rate of 94.76%. Parallel trapping and alignment of Shigella are also conducted.